IMMU-24. IMPROVING OUTCOMES IN OLDER ADULTS WITH GLIOBLASTOMA BY REVERSING AGE-RELATED CHANGES. (12th November 2021) - Ladomersky, Erik; Zhai, Lijie; Bollu, Lakshmi; Bell, April; Lauing, Kristen; Lukas, Rimas; Wainwright, Derek
Abstract: Wild-type IDH glioblastoma (wtGBM) represents ≥90% of human GBM patient diagnoses with a median age of onset at 68-70 years of age. We previously found a decline of GBM patient survival with progressive age and that subjects ≥65 years of age had the poorest prognosis. We also showed an age-dependent enhancement of immune suppression in the brain that negatively affected immunotherapeutic efficacy in older adult mice with syngeneic brain tumors. Here, we extended those observations while studying C57BL/6 mice with intracranial CT-2A or GL261 between 80-110 weeks old - analogous to the age of a wtIDH GBM patient diagnosis. Overall survival of older adult mice with CT-2A or GL261 was significantly decreased when subjects were lymphopenic for CD4 + T cells as compared to an IgG Ab treatment group (n=12/group; p < 0.01). CD8 + T cell or NK cell leukopenia had no effect on survival outcomes. The negative effect of CD4 + T cell lymphopenia in older adults was not observed in younger mice with brain tumors. We also investigated the increased immunosuppression in the brain and its relationship to the accumulation of senescent cells and the treatment with standard of care radiation/temozolomide (RT/TMZ). p16INK4A, a marker for senescent cells, was increased in non-tumor cells of the brain during advanced age and its expression was increased after treatment with RT/TMZ. Older adult mice with brain tumors and treated with senolytics showed decreased p16INK4A levels after treatment with RT/TMZ. Senolytic treatment also improved the efficacy of combination therapy with RT, anti-PD-1 mAb, and IDO enzyme inhibitor in older adults as compared to senolytics alone or the triple immunotherapeutic cocktail alone (n=12-15/group; p < 0.01). Collectively, the results suggest that strategies aimed at reversing the effects of the aging combined with tumor eradication therapies may be particularly beneficial for older adult human patients with GBM.